Analisis Kemampuan Pemahaman Konsep Matematis Siswa MAN 1 Sungai Penuh Pada Materi Bangun Ruang - Eline Yanty Putri Nasution; Atika Rahayu (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2023)
The background of this research was lowerness of th students’ conceptual understanding ability in mathematics. The purpose of this study was to describe the students' mathematical conceptual understanding ability in geometry material. The type of this study is descriptive qualitative research. The subjects of this research were 26 students of XI IPA 2 grade in MAN 1 Sungai Penuh. The data collection techniques used include: (1) test of mathematical conceptual understanding ability; (2) observation sheet; (3) interview; and (4) documentation. The results of this study indicate that the average of students' mathematical conceptual understanding ability is 89,65 with very good category. From the seven indicators there are four indicators with very good category, namely restating a concept, presenting concepts in various forms of mathematical representations, developing necessary or sufficient requirements of a concept, and apply the concept or problem-solving algorithm. There is one indicator with good category, namely classify objects according to certain properties according to the concept. Then there are two indicators with enough category, namely provide examples and non-examples and use, utilize, and select certain procedures.